2016
DOI: 10.1007/s13595-016-0572-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving the design of long-term monitoring experiments in forests: a new method for the assessment of local soil variability by combining infrared spectroscopy and dendrometric data

Abstract: Abstract& Key message Near-and mid-infrared spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…confirmed by NIR-MIR spectroscopy without preliminary calibration, which provided an overall view of the soils. Because NIR and MIR spectra reflect a set of soil constituents that can be determined simultaneously, the use of raw spectra alone has been proposed previously to monitor soil properties in an integrative way to discriminate between different levels of an ecological factor (Cécillon et al, 2009;Akroume et al, 2016). However, this issue remains controversial (Terhoeven-Urselmans et al, 2006;Viscarra Rossel et al, 2006;Ludwig et al, 2008Ludwig et al, , 2015, and these techniques should be used in combination with calibration and multivariate regression methods to obtain a precise characterization of the soil properties of experimental sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…confirmed by NIR-MIR spectroscopy without preliminary calibration, which provided an overall view of the soils. Because NIR and MIR spectra reflect a set of soil constituents that can be determined simultaneously, the use of raw spectra alone has been proposed previously to monitor soil properties in an integrative way to discriminate between different levels of an ecological factor (Cécillon et al, 2009;Akroume et al, 2016). However, this issue remains controversial (Terhoeven-Urselmans et al, 2006;Viscarra Rossel et al, 2006;Ludwig et al, 2008Ludwig et al, , 2015, and these techniques should be used in combination with calibration and multivariate regression methods to obtain a precise characterization of the soil properties of experimental sites.…”
Section: Discussionmentioning
confidence: 99%
“…The MIR method is assumed to be a suitable predictor for organic matter composition, whereas the NIR one is commonly used to predict soil C and N stocks (Ludwig et al, 2008;Soriano-Disla et al, 2014). However, these assumptions are still under debate and the combined use of NIR and MIR is recommended for more efficient characterization of soil (Viscarra Rossel et al, 2006;Akroume et al, 2016). Compared with MIR, the total NIR spectrum showed the effect of tree genotype better on our soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Achat et al (2015b) indicated that long term impact of intensive forestry remains poorly examined and notably on soil microbial compartment. In the present study, we measured soil parameters and associated microbial functions in six temperate beech forest sites of a new long-term observational French network, comparing OM removal treatment and conventional forest management (Akroume et al, 2016). This large-scale investigation aims to mimic the effect of middle / long-term OM removal thanks artificial and annual exportation of woody debris and litter layer (Stone, 2001).…”
Section: Introductionmentioning
confidence: 99%